2020
DOI: 10.2147/dddt.s228721
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-Inflammatory Activity of Sanjie Zhentong Capsule Assessed By Network Pharmacology Analysis of Adenomyosis Treatment </p>

Abstract: Background: Sanjie Zhentong capsule (SZC) offers excellent effect in treating adenomyosis (AM), which is a common and difficult gynecological disease in the clinic. However, the systematic analysis of its mechanism has not been carried out yet and further studies are needed to reveal the role of SZC. Methods: A systematic network pharmacology analysis was conducted by integrating construction of SZC compound database and AM target database, prediction of potential active compounds and targets by molecular dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…According to the theory of TCM, "blood stasis" is the core pathogenesis of AM (Bi, 2020), resulting in the progressive exacerbation of dysmenorrhea in AM (Imanaka et al, 2021;Alcalde et al, 2022). TCM for promoting blood circulation has been shown to alleviate AM dysmenorrhea symptoms, reduce menstrual volume, and lower CA125 levels (Du and Du, 2020) (Zi et al, 2020) (Wang H Y et al, 2018). Dahuang -Taoren (DT), a classic botanical drug combination to combat "blood stasis," is clinically used for AM treatment in China.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theory of TCM, "blood stasis" is the core pathogenesis of AM (Bi, 2020), resulting in the progressive exacerbation of dysmenorrhea in AM (Imanaka et al, 2021;Alcalde et al, 2022). TCM for promoting blood circulation has been shown to alleviate AM dysmenorrhea symptoms, reduce menstrual volume, and lower CA125 levels (Du and Du, 2020) (Zi et al, 2020) (Wang H Y et al, 2018). Dahuang -Taoren (DT), a classic botanical drug combination to combat "blood stasis," is clinically used for AM treatment in China.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of TCM in treating AM has been confirmed through several hundred years' practices and experimental research [ 11 ]. Previous studies have found that TCM treatment can alleviate dysmenorrhea, shorten the menstrual time, decrease menstrual volume, reduce uterine volume, and lower CA125 levels in AM patients [ 12 – 14 ]. GZFLW is one of the classic traditional Chinese herbal formulas widely used in the clinical treatment of AM [ 8 ], and studies have confirmed that the side effect of GZFLW on AM is only 1.99% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Cytoscape3.8.0 (http://www.cytoscape.org/) was used for analysis to construct the component‐target‐disease network. [ 19–21 ]…”
Section: Methodsmentioning
confidence: 99%
“…cytoscape.org/) was used for analysis to construct the componenttarget-disease network. [19][20][21] Gene pathway analysis: The DAVID (the Database for Annotation, Visualization, and Integrated Discovery) database (http://david. abcc.ncifcrf.gov/) is an online, freely available bioinformatics database for differential gene functional and pathway enrichment analysis.…”
Section: Network Pharmacology Studiesmentioning
confidence: 99%